MEMAKSIMALKAN FITUR VIRTUAL BASIC FOR APPLICATION PADA MS. POWERPOINT DALAM PEMBUATAN KUIS INTERAKTIF DAN MEDIA BELAJAR - Purwasih, Silviana Maya; Prayitno, Lydia Lia; Faizah, Hanim; Maftuh, Moh. Syukron (Universitas PGRI Adi Buana Surabaya, 2022)
It is important for students to use educational media appropriately in order to achieve successful learning outcomes. According to observations observed at SMP PGRI Buduran, learning media are not used optimally in the classroom despite the school providing a computer with an access to the internet. In order to implement one of the Tri Dharma of Higher Education, the PPM team at PGRI Adi Buana University collaborates with SMP Negeri 1 Buduran Sidoarjo teachers in preparing mathematics learning media by maximizing the powerpoint features. During this activity, the PPM Team used various PowerPoint features to create learning materials, interactive quizzes, and evaluation tools, including the VBA feature, which is still very rarely used. The training was conducted well, and all participants listened and participated enthusiastically.